Cultural Discontinuity as a Major Problem of Rai Students’ Learning of Mathematical - Pokharel, Jagat Krishna (Innovative Research Journal, 2023)
This study explores the impact of cultural diversity and discontinuity on the learning of mathematics by Rai students in community schools, and its correlation with student dropout rates. The research utilized interviews, observations, diaries, and field notes to gather data, which were subsequently analyzed thematically. Findings indicate that cultural factors, socio-economic status, language differences, and gender roles significantly influence the Rai students’ academic performance and engagement, particularly in mathematics. This cultural discontinuity between home and school environments, alongside societal and teacher behaviors, impedes their learning process. The article recommends implementing culturally inclusive teaching strategies and enhancing teacher sensitivity to the students’ diverse backgrounds to improve educational outcomes.